Influence of hydrogen addition on lean premixed methane-air flame statistics - (:unkn) unknown (My University, 2010)
Hydrogenated premixed methane/air flames under lean conditions are simulated in this study. The computational model of the high pressure chamber setup of Orleans - ICARE (France) has been developed. The k-ε turbulence model with Pope-correction is used for turbulence modeling. The laminar flame properties are computed using GRI-Mech 3.0 mechanism with Chemkin software package. The turbulent flame front statistics are investigated with three premixed combustion models, namely Zimont, Coherent Flame Model (CFM) and modified version of CFM model (MCFM) models. It has been observed that increasing the volumetric percentage of hydrogen in the mixture results in reducing the flame-end position. The flame brush thickness becomes thinner as well. Satisfactory results have been obtained compared to experiments. Copyright © 2010 by ASME.